2021
DOI: 10.1002/ajhb.23596
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte telomere length is inversely associated with a metabolic risk score in Mesoamerican children

Abstract: Objective Leukocyte telomere length (LTL) may be involved in the etiology of the metabolic syndrome (MetS). We examined the associations of LTL with MetS and its components among Mesoamerican children and their adult parents, in a region where MetS prevalence is high. Methods We conducted a cross‐sectional study of 151 children aged 7–12 years and 346 parents from the capitals of Belize, Honduras, Nicaragua, Costa Rica, Panama, and Chiapas State, Mexico. We quantified LTL by qPCR on DNA extracted from whole bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
(66 reference statements)
1
2
0
Order By: Relevance
“…12 In another cross-sectional study of school-age children, WC strongly predicted LTL in girls but not boys, 13 consistent with our main finding. Similarly, LTL was inversely related to WC in a cross-sectional study of Mesoamerican children, 14 in agreement with our results for girls. Additionally, in an intervention programme for adolescents with overweight or obesity, longer LTL at baseline predicted larger weight loss.…”
Section: Discussionsupporting
confidence: 92%
“…12 In another cross-sectional study of school-age children, WC strongly predicted LTL in girls but not boys, 13 consistent with our main finding. Similarly, LTL was inversely related to WC in a cross-sectional study of Mesoamerican children, 14 in agreement with our results for girls. Additionally, in an intervention programme for adolescents with overweight or obesity, longer LTL at baseline predicted larger weight loss.…”
Section: Discussionsupporting
confidence: 92%
“…As shorter LTL is associated with systemic oxidative stress exposure and severity of metabolic disease, it is possible that our finding of longer LTL with increasing amounts of lobular inflammation may suggest alternate pathways, including potential future risk for cancer in these children 30,31 . Long-term longitudinal studies of pediatric patients with NAFLD have not yet been conducted.…”
Section: Discussionmentioning
confidence: 95%
“…Regarding the intensity of PA, the findings are controversial. In the context of obesity, several exercise interventions assessed the possible role of PA on TL [ 40 , 44 ], but just one showed significant results [ 44 ]. Sjögren et al found that a decrease in sitting time during weekdays was associated with longer TL in older adults who were overweight [ 43 ].…”
Section: Discussionmentioning
confidence: 99%